The Anti-Inflammatory Effect of Cabbage Leaves Explained by the Influence of bol-miRNA172a on FAN Expression - Kasarello, Kaja; Köhling, Iwona; Kosowska, Anna; Pucia, Katarzyna; Lukasik, Anna; Cudnoch-Jedrzejewska, Agnieszka; Paczek, Leszek; Zielenkiewicz, Urszula; Zielenkiewicz, Piotr (Frontiers in Pharmacology, 2022)
Recently, the possibility of cross-kingdom gene expression regulation by miRNAs from other species (“xenomiRs”), specifically from plants, has acquired scientific meaning. Based on the one of oldest methods for dealing with inflammation via the use of cabbage leaf compresses, we investigated the effects of Brassica oleracea derived miR172a on the potential human target gene encoding FAN (Factor Associated with Neutral Sphingomyelinase Activation) protein. In vitro experiments showed a decrease in FAN protein levels in both human and mouse cells transfected with bol-miRNA172a. As the FAN protein mediates inflammatory responses, the potential of miR172a to mitigate the inflammatory process was tested in a mouse model of rheumatoid arthritis. Animal studies showed the decreased oedema of inflamed paws in mouse with rheumatoid arthritis model induced after treatment with miR172a.